Elektrolytische Messung von Stoffaustauschkoeffizienten - P. Grassmann (CHIMIA)
Under certain circumstances the current trough an electrolytic cell is dependent on mass transfer to the cathode only. Utilizing this fact a method for measuring local and instantaneous mass transfer coefficients had been developed at the Institute of Chemical Engineering and Refrigeration. This method was applied to measure the local distribution of mass transfer and turbulence on cylinders and spheres by forced and free convection, the mass transfer near a growing bubble as a function of time and distance and other problems of interest for chemical engineering.